Exploring the harms arising from polysubstance use among performance and image enhancing drug users among young Australian men. Issue 3 (October 2021) - Piatkowski, Timothy M; Dunn, Matthew; White, Katherine M; Hides, Leanne M; Obst, Patricia L
Abstract: Evidence suggests young men who use performance and image enhancing drugs (PIEDs) in Australia also engage in alcohol and party drug use. Such polysubstance use is concerning as it could exacerbate the harms that come from using either PIEDs or other drugs alone. The present study employed semi-structured interviews with 12 young men which aimed to explore patterns of PIED and other drug use among a sample of young men who use PIEDs in Australia. Analysis of interview data identified typical patterns of PIED use and other drug use among this group. The analysis yielded two themes: 1) extent of compound use for body enhancement and 2) alcohol and other drug use resulting in harms for PIED users. The present findings underscore that young men who use PIEDs represent an at risk population for alcohol and party drug use and the increased array of harms that the combination of multiple substances produces.